Strategi Pengembangan Koperasi Dengan Analisis SWOT - Mohammad Hatta Fahamsyah; Afif Mustafid Taftazani; Listian Indriyani Ahmad (STIKes Ibnu Sina Ajibarang, 2024)
This training on SWOT Evaluation for Cooperative Development is intended to increase the enthusiasm, knowledge, skills and capabilities of the Management, Head of Business Units and Chair of the Simprug Garden Cooperative in managing and developing cooperative businesses. The approach to implementing this activity includes material presentations, question and answer sessions, and group discussions (FGD) regarding business development strategies by applying SWOT analysis. Training material includes SWOT analysis, cooperative management, cooperative business management, cooperative management values, and business development strategies. A total of 20 training participants, consisting of the Management, Head of the Simprug Garden Cooperative Business Unit, and cadre members, participated in this activity. Evaluation is carried out through pre-test and post-test material as well as assessment of the results of Group Discussions related to